Meaning of “Speculation“ and “Speculator“ in Lithuanian SSR (1940–1941) - Indrišionis, Darius (Lietuvos istorijos studijos, 2023)
This research focuses on anti-speculation propaganda of Soviet regime in the years of First Soviet Occupation of Lithuania (1940–1941). Image of various speculation aproaches is analised as well as public communication of Soviet regime while installing radical social and economical reforms (widespread nacionalization of different types of property, mostly). Also, this research shows that the “campaign against speculation” inspired by Soviet regime had some antisemitic content: when in the first months of occupation almost every day there were lists of speculators published in newspapers, these lists were dominated by Jewish names and surnames. That tendency could not lead to a rising of an antisemitic views in Lithuanian society. By the way, this research describes how Soviet regime widened a term “speculator”: while in the beginning of occupation it mostly could mean only a person who is mixed up in illegal trading activities, in the beginning of the summer of 1941 this term demonstrated a negative view of Soviet regime to any entrepreneurship initiative that is coming not from the officials of the regime.